Best friends and drama queens - Cabot, Meg. (New York : Scholastic Press, 2009)
Nine-year-old Allie Finkle's list of rules helps her navigate a tricky situation with a new girl at school.
Keywords: Schools -- Fiction; Rules (Philosophy) -- Fiction; Behavior -- Fiction; Best friends -- Fiction; Friendship -- Fiction